Kinetics of emulsifier-free emulsion polymerization of methyl methacrylate - Tanrisever, T; Okay, O; Sonmezoglu, IC (JOHN WILEY & SONS INC, 1996)
The influences of polymerization temperature, initiator and monomer concentrations, ionic strength of the aqueous phase, as well as ethylene glycol dimethacrylate (EGDM) comonomer, on the kinetics of the emulsifier-free emulsion polymerization of methyl methacrylate (MMA) and on the properties of the resulting poly(methyl methacrylate) (PMMA) lattices were studied. The polymerizations were carried out using potassium persulfate (KPS) as the initiator. Monodisperse PMMA lattices with particle diameters varying between 0.14-0.37 mu m and polymer molecular weights of the order 0.4 x 10(6) to 1.2 x 10(6) g/mol were prepared. The initial rate of polymerization increases with increasing temperature, KPS-MMA mole ratio, EGDM content, or with decreasing ionic strength of the aqueous phase. It was shown that the bead size can be limited by reducing the monomer concentration or by using the cross-linking agent EGDM. The ionic strength of the aqueous phase has a dominant effect on final particle diameter and polymer molecular weight. The uniformity of the latex particles increases as the temperature increases or as the initiator concentration decreases. The experimental results can be reasonably interpreted by the homogeneous nucleation mechanism of the emulsifier-free emulsion polymerization of MMA. (C) 1996 John Wiley & Sons, Inc.
Keywords: AQUEOUS-PHASE POLYMERIZATION; MODEL FILLED POLYMERS; STYRENE; NUCLEATION; ACRYLATE; BEADS; Polymer Science